Homocysteine impairs porcine oocyte quality via deregulation of one-carbon metabolism and hypermethylation of mitochondrial DNA†. Issue 4 (3rd November 2018) - Jia, Longfei; Zeng, Yaqiong; Hu, Yun; Liu, Jie; Yin, Chao; Niu, Yingjie; Wang, Chenfei; Li, Juan; Jia, Yimin; Hong, Jian; Zhao, Ruqian
Abstract: Homocysteine (Hcy) is an intermediate in the one-carbon metabolism that donates methyl groups for methylation processes involved in epigenetic gene regulation. Although poor oocyte quality in polycystic ovarian syndrome (PCOS) patients is associated with elevated Hcy concentration in serum and follicular fluid, whether Hcy directly affects oocyte quality and its mechanisms are poorly understood. Here we show that Hcy treatment impaired oocyte quality and developmental competence, indicated by significantly reduced survival rate, polar body extrusion rate, and cleavage rate. Hcy treatment resulted in mitochondrial dysfunction, with increased production of mitochondrial ROS, reduced mtDNA copy number, and the expression of 7 out of 13 mtDNA-encoded genes and 2 ribosome RNA genes, 12S rRNA and 16S rRNA . Upon Hcy treatment, the expression of one-carbon metabolic enzymes and DNMT1 was enhanced. Interestingly, DNA methyltransferase inhibitor 5′AZA rescued Hcy-induced mitochondrial dysfunction, impaired oocyte quality and developmental competence. Concurrently, expression of one-carbon metabolic enzymes and methylation status of mtDNA coding sequences were also normalized, at least partially, by 5′AZA treatment. Our findings not only extend the understanding about how Hcy induces poor oocyte quality, but also contribute to a novel angle of identifying targets for enhancing the quality of oocyte from PCOS patients. Abstract : Homocysteine disrupts one-carbon metabolism, which leads to hypermethylation of mitochondrial DNA, mitochondrial dysfunction, and impaired oocyte quality.